Elaboración de compost a partir de residuos orgánicos, vegetales y animales - Nacarino Velez, Adolfo Guillermo (2006)
The municipal solid remainders generated in the city of Santiago of Chuco are: remainders of processing of food, animal dung, remainders of grass, papers, garden remainders, plastics and glass that constitute an ecological problem; then its present disposition in containers to opened sky, they are a source of risks for the health of the settlers. The solid remainders were collected, classified and characterized physical-chemical and the organic matter it was tried for its conversion in Compost in small scale with the help of parasites, controlling humidity parameters (42%), pH (5,8 - 8), temperature (65%), relation carbon/nitrogen (16) and amount of nutrients. One concludes with establishing that compost elaborated is apt to be used like fertilizer and reconditioning of grounds in the city of Santiago of Chuco